Chemical and physical properties of Aloe vera (Aloe barbadensis Miller) gel stored after high hydrostatic pressure processing - Di Scala, Karina Cecilia (2012)
&e aim of this study was to evaluate the in[uence of high hydrostatic pressure (150, 250, 350, 450, and 550 MPa), applied for 5 minutes, on antioxidant capacity, total phenolic content, color, Frmness, rehydration ratio, and water holding capacity of aloe vera gel stored for 60 days at 4 °C. &e analyzed properties of the pressurized gel showed signiFcant changes a\er the storage period. &e highest value of total phenolic content was found at 550 MPa. However, a decrease in the antioxidant capacity was observed for all pressurized gel samples when compared to the control sample (p < 0.05). &e smallest changes in product color were observed at pressure levels between 150 and 250 MP. &e application of high hydrostatic pressure resulted in lower gel Frmness, and the lowest value was found at 150 MPa (p < 0.05). On the other hand, the untreated sample showed a greater decrease in Frmness, indicating that high pressure processing preserves this property. &e application of high hydrostatic pressure exhibited modiFcations in the food matrix, which were evaluated in terms of rehydration ratio and water holding capacity.